Comprehensive performance enhancement of a negative-capacitance nanosheet field-effect transistor with a steep sub-threshold swing at the sub-5-nm node. (February 2022) - Lü, Weifeng; Chen, Xianlong; Liu, Bo; Xie, Ziqiang; Guo, Mengxue; Zhao, Mengjie
Abstract: A nanosheet field-effect transistor (NSFET), which has excellent gate control ability, has been considered as the most attractive key architecture that may replace the FinFET below a 5-nm technology node. In this study, a three-dimensional (3D) technology computer-aided design (TCAD) simulation is carried out to evaluate and compare the performance of a negative-capacitance NSFET (NC-NSFET) with an NC fin field-effect transistor (NC-FinFET). The result shows that under the same structural parameters, the NC-NSFET has a higher on-current- to-off-current ratio ( I on / I off ), and lower sub-threshold swing (SS) and drain-induced barrier lowering (DIBL) than the NC-FinFET. The analog/radio frequency (RF) performance enhancement of the NC-NSFET shows that the NC-NSFET has higher transconductance ( g m ) and cutoff frequency ( f T ) at a lower drain voltage ( V ds ) than the conventional NSFET has. In addition, a negative correlation between f T and SS, which is determined and verified for the first time, reveals that the NC-NSFET enabling analog/RF performance improvement is attributed to the higher ratio of the drain current to the SS.